Reflective Teaching Perception of EFL Teachers Who Applied Reflective Teaching Tools in Their Class - Köksal, Özge (Özgür Yayınları, 2024)
Reflective teaching, which has gained popularity and reattracted scholarly interest recently, can help practitioners of education gain new insights into their own practices by questioning their underlying assumptions, habits and perspectives and taking broader societal and political implications of their teaching. In a world where change has become an undeniable aspect of daily life, reflective teaching is particularly important considering its possible far-reaching contributions to the overall quality of teaching. Grounded in a mixed method embedded design, the current study was carried out to explore (1) overall levels of reflection of the participants, (2) whether certain variables (gender, degree, experience, certification and department) have an influence on the participants' levels of reflection, (3) how reflection takes place, (4) what tools of reflection are employed by the participant. For the current study, the quantitative data was collected through the Reflective Teaching Questionnaire developed by Larrivee (2008). The questionnaire was administered to 100 instructors employed in the foreign languages departments of eight foundation universities in Turkey. The data obtained were analyzed using SPSS (26) for Windows. The qualitative study followed the quantitative phase and was carried out with the participation of 10 instructors in one of the foundation universities. The qualitative data was collected through the semi-structured individual interviews and content-analyzed by the researcher manually. The findings revealed that the participants' perception of their reflection levels were positive. The results indicated that the majority of the participants reflected on their teaching pedagogically or critically, though in many cases the variables of the study did not seem to significantly affect their levels of reflection. The qualitative findings also indicate that reflection takes place before, during or after teaching, and diverse reflection tools are used by the participants. The qualitative findings also indicate that there are some contextual factors inhibiting or enabling reflection such as strict curriculum, workload, work environment and flexibility. When both the qualitative and quantitative data are considered together, it seems that the participants' perception of their reflective practices are positive, but it is also clear from the results that reflection does not happen in a systematic and organized way. Finally, it is noteworthy to state that reflection levels seem to be dependent most on individual factors and choices, regarding that such variables as degree, experience, certification and experience often did not significantly impact reflection levels. To conclude, the present study contributes modest insights into reflective teaching practices in higher education ELT/EFL settings. Acknowledging the positive implications of reflection, the findings of the study related to how reflection takes place and what tools are used can help both researchers and practitioners in the field understand reflective teaching better.